Implementation Strategy of Knowledge Management System: A Case of Air Drilling Associates - Siti Hadjar; Putu Wuri Handayani; Riri Satria; Ave Adriana Pinem (IAES Indonesia Section, 2018)
Just as companies in the oil and gas industry, Air Drilling Associates (ADA) also feel the urgency to utilize Knowledge Management to facilitate resilience in a dynamic and competitive business environment. By the end of 2016 ADA introduces the ADA Knowledge Base, a Knowledge Management System, for employee to be utilized as a platform for sharing experiences and learning. However, up to one year since its introduction, the employee participation rate against ADA Knowledge Base is still low. A strategy is required for the implementation of a Knowledge Management System that is part of support for Knowledge Management. This study conducted by using Soft System Methodology approach and Knowledge Management theory. Respondents upper management, middle management and staff form the organization has been interviewed. The result defined three steps and sixteen activities for the company to implement the Knowledge Management System.